2020
DOI: 10.1038/s41598-020-77904-3
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated quantitative comparison of metal artifact reduction in photon-counting computed tomography by energy-selective thresholding

Abstract: An evaluation of energy thresholding and acquisition mode for metal artifact reduction in Photon-counting detector CT (PCD-CT) compared to conventional energy-integrating detector CT (EID-CT) was performed. Images of a hip prosthesis phantom placed in a water bath were acquired on a scanner with PCD-CT and EID-CT (tube potentials: 100, 120 and 140 kVp) and energy thresholds (above 55–75 keV) in Macro and Chess mode. Only high-energy threshold images (HTI) were used. Metal artifacts were quantified by a semi-au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…Do et al, (2020) compared different energy thresholds and acquisition modes for PCD-CT and EID-CT after scanning a hip prosthesis phantom. Fewer metal artifacts were found in high-energy threshold images compared to low-energy thresholds and the choice of acquisition mode had an influence on the number of artifacts seen in relevant structures such as cortical bone and bone marrow [ 26 ]. These findings warrant further investigation in future studies in order to corroborate the findings of this study and to identify the ideal settings for postoperative CI imaging with the novel PCD-CT technology.…”
Section: Discussionmentioning
confidence: 99%
“…Do et al, (2020) compared different energy thresholds and acquisition modes for PCD-CT and EID-CT after scanning a hip prosthesis phantom. Fewer metal artifacts were found in high-energy threshold images compared to low-energy thresholds and the choice of acquisition mode had an influence on the number of artifacts seen in relevant structures such as cortical bone and bone marrow [ 26 ]. These findings warrant further investigation in future studies in order to corroborate the findings of this study and to identify the ideal settings for postoperative CI imaging with the novel PCD-CT technology.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamentally, the direct-conversion PCD technology enables uniform photon weighting across x-ray energies, small detector-pixel design, and energy thresholding and photon binning for multi-energy imaging. This has led to superior imaging capabilities compared to conventional CT which uses energy integrating detectors (EIDs), such as elimination of electronic noise ( Yu et al, 2016b ), facilitation of ultra-high resolution (UHR) imaging using smaller detector pixels ( Leng et al, 2016 , Pourmorteza et al, 2018 ), reduction of metal artifacts ( Do et al, 2020 , Zhou et al, 2019 ), and improvement of iodine contrast-to-noise ratio ( Gutjahr et al, 2016 , Schmidt, 2009 ). In addition, the energy-binning feature of PCDs allows measurements above and below the K-edge of high-Z materials.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations involving a whole-body research PCD-CT system built using a modified 2 nd generation dual-source CT platform, with the B-subsystem equipped with a CdTe PCD array ( Kappler et al, 2014 , Leng et al, 2018 , Pourmorteza et al, 2016 , Symons et al, 2016 , Yu et al, 2016a ), have shown superior imaging performance relative to EID-CT in phantoms, animals, and patients. In humans, this system has demonstrated dose-efficient ultra-high resolution (UHR) imaging without comb/grid filters ( Bartlett et al, 2019 , Leng et al, 2016 , Pourmorteza et al, 2018 ), radiation dose reduction ( Klein et al, 2020 , Rajendran et al, 2020 , Symons et al, 2016 ), metal artifact reduction using high-energy thresholding and a tin filter ( Do et al, 2020 , Zhou et al, 2019 ), and multi-energy capabilities ( Leng et al, 2018 , Pourmorteza et al, 2016 , Symons et al, 2018 ) focusing on neurological, musculoskeletal, thoracic, vascular and abdominal imaging applications. Additionally, phantom and animal studies using this system have shown the potential for multi-contrast imaging ( Ren et al, 2020 , Symons et al, 2017 ) and improved stent delineation ( Mannil et al, 2018 , von Spiczak et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another metal artifact-reduction technique is the reconstruction of an image using only photons measured over 70 keV. The resulting high-threshold image presents an increased CNR compared to conventional images in presence of metal artifacts [26]. The optimal weight for differentiating calcium from water is derived from the attenuation coefficients subtraction (dashed lines).…”
Section: Spectral Modementioning
confidence: 99%
“…Another metal artifact-reduction technique is the reconstruction of an image using only photons measured over 70 keV. The resulting high-threshold image presents an increased CNR compared to conventional images in presence of metal artifacts [26].…”
Section: Virtual Monoenergetic (Vmi) Imagesmentioning
confidence: 99%